Computation of energy absorption and residual voltage in a fourth rail LRT station arresters in EMTP-RV: a comparative study - Abd Rahman, Farah Asyikin; Ab Kadir, Mohd Zainal Abidin; Ungku Amirulddin Al Amin, Ungku Anisa; Osman, Miszaina (Springer, 2021)
This paper presents a study on the performance of a fourth rail direct current (DC) urban transit affected by an indirect lightning strike. The indirect lightning strike was replicated and represented by a lightning-induced overvoltage by means of the Rusck model, with the sum of two Heidler functions as its lightning channel base current input, on a perfect conducting ground. This study aims to determine whether an indirect lightning strike has any influence with regard to the performance of the LRT Kelana Jaya line, a fourth rail DC urban transit station arrester. The simulations were carried out using the Electromagnetic Transients Program–Restructured Version (EMTP–RV), which includes the comparison performance results between the 3EB4-010 arrester and PDTA09 arrester when induced by a 90 kA (9/200 µs). The results demonstrated that the PDTA09 arrester showed better coordination with the insulated rail bracket of the fourth rail. It allowed a lower residual voltage and a more dynamic response, eventually resulting in better voltage gradient in the pre-breakdown region and decreased residual voltage ratio in the high current region.